A picture book of Florence Nightingale - Adler, David A.; Wallner, John C.; Wallner, Alexandra (New York : Holiday House, 1992)
Traces the life of the nineteenth-century English woman who followed her calling to work in hospitals and improve the conditions under which the sick were treated.
Adult 760
Accelerated Reader AR
Keywords: Nightingale, Florence, -- 1820-1910 -- Pictorial works -- Juvenile literature; Nightingale, Florence, -- 1820-1910.; Nurses -- England -- Biography -- Pictorial works -- Juvenile literature; Nurses